Evaluation and Comparison of Three Types of Spray Dried Coprocessed Excipient Avicel® for Direct Compression - Vodáčková, Pavlína; Vraníková, Barbora; Svačinová, Petra; Franc, Aleš; Elbl, Jan; Muselík, Jan; Kubaľák, Roman; Solný, Tomaš (BioMed research international, 2018)
As coprocessed excipients (CPE) gain a lot of focus recently, this article compares three commercially available CPE of Avicel brand, namely, CE 15, DG, and HFE 102. Comparison is based on measured physical properties of coprocessed mixtures, respectively, flow properties, pycnometric density, mean particle size, specific surface area, moisture content, hygroscopicity, solubility, pH leaching, electrostatic charge, SEM images, and DSC. Tablets were made employing three pressure sets. Viscoelastic properties and ejection force were assessed during compression, as well as pycnometric density, mass uniformity, height, tensile strength, friability, disintegration, and wetting times. Avicel CE 15 is of mid-range flow properties, contains mid-size and nonspherical particles, and has high hygroscopicity, growing negative charge, best lubricity, lowest tensile strength, and mid-long disintegration times. Avicel DG possesses the worst flow properties, small asymmetrical particles, lowest hygroscopicity, stable charge, intermediate lubricity, and tensile strength and exhibits fast disintegration of tablets. Finally, Avicel HFE 102 has the best flow properties, large symmetrical particles, and middle hygroscopicity and its charge fluctuates throughout blending. It also exhibits inferior lubricity, the highest tensile strength, and slow disintegration of tablets. Generally, it is impossible to select the best CPE, as their different properties fit versatile needs of countless manufacturers and final products.
Keywords: Cellulose; Compressive Strength; Pressure; prášky, zásypy, pudry; pomocné látky; Water; voda; tlak; poréznost; Humidity; vlhkost; koncentrace vodíkových iontů; rozpustnost; Desiccation; tablety; Static Electricity; diferenciální skenovací kalorimetrie; Solubility; reologie; Tablets; Calorimetry, Differential Scanning; fyzikální absorpce; velikost částic; Excipients; pevnost v tlaku; Wettability; Rheology; statická elektřina; vysoušení; Hydrogen-Ion Concentration; pevnost v tahu; Absorption, Physicochemical; Particle Size; smáčivost; Powders; časové faktory; celulosa; Tensile Strength; Porosity; Time Factors